2013
DOI: 10.3390/metabo3010047
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the Metabolites of 1,8-Cineole Transferred into Human Milk: Concentrations and Ratio of Enantiomers

Abstract: 1,8-Cineole is a widely distributed odorant that also shows physiological effects, but whose human metabolism has hitherto not been extensively investigated. The aim of the present study was, thus, to characterise the metabolites of 1,8-cineole, identified previously in human milk, after the oral intake of 100 mg of this substance. Special emphasis was placed on the enantiomeric composition of the metabolites since these data may provide important insights into potential biotransformation pathways, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 51 publications
(92 reference statements)
1
28
0
Order By: Relevance
“…Similar findings were reported using isolated rat and human liver microsomes [40,41]. More extensive safety measurements are necessary to evaluate 1,8-cineole, however, subacute hepato-and nephro-toxicity was reported with only high doses (500-1000 mg/kg body weight) [42,43]. LD50 value in rats is 2.5 g oral dose/kg body weight [44], which is considerably higher than the reported effective therapeutic dosing (see below) suggesting that 1,8-cineole is likely to be safe as a therapeutic modality.…”
Section: Chemical Properties Of 18-cineolesupporting
confidence: 69%
“…Similar findings were reported using isolated rat and human liver microsomes [40,41]. More extensive safety measurements are necessary to evaluate 1,8-cineole, however, subacute hepato-and nephro-toxicity was reported with only high doses (500-1000 mg/kg body weight) [42,43]. LD50 value in rats is 2.5 g oral dose/kg body weight [44], which is considerably higher than the reported effective therapeutic dosing (see below) suggesting that 1,8-cineole is likely to be safe as a therapeutic modality.…”
Section: Chemical Properties Of 18-cineolesupporting
confidence: 69%
“…Our dose–response analysis revealed that eucalyptol is a significantly more potent agonist of human TRPM8 channels (EC 50 = 120.4 μM) than of mouse TRPM8 channels (EC 50 = 924.5 μM) or rat TRPM8 channels (EC 50 = 1.21 mM), suggesting that the lower dosages of eucalyptol used in human clinical trials may indeed be sufficient to activate human TRPM8 channels and counteract inflammation, even when administered when inflammation is already established. Eucalyptol and its metabolites can still be detected at significant levels in human body fluids, some hours after dosing (Kirsch and Buettner, ). Some of eucalyptol's major metabolites such as 2‐hydroxy‐1,8‐cineol used in the present study structurally resemble eucalyptol and menthol (Madyastha and Chadha, ; Horst and Rychlik, ).…”
Section: Discussionmentioning
confidence: 99%
“…Human metabolism of 1,8‐cineole was investigated in vitro and in vivo by Duisken et al 82. In vitro, the biotransformation of 1,8‐cineole was investigated using human liver microsomes and recombinant CYP3A4 and CYP3A5 coexpressed with human CYP reductase in Escherichia coli cells.…”
Section: Biooxidation Of 18‐cineole In Animals and Humansmentioning
confidence: 99%